Mixed-mode thermal fracture of AISI 304 stainless steel with temperature-dependent material properties - Rajabi, M.; Soltani, N. (Archives of Mechanics, 2016)
Mixed-mode thermal fracture of cracked AISI 304 austenitic stainless steel layers under severe thermal gradients of cryogenic and elevated temperatures is studied. Taking into account the variation of thermo-mechanical properties with temperature, the Jk-integral method, incorporating temperature-dependent material properties, is used to determine mixed-mode stress intensity factors from the results of finite element (FE) analysis. Effects of the convection heat transfer coefficient and the temperature of the contacting fluid on the mixed-mode fracture of the steel layers are investigated and it is shown that the mixed-mode stress intensity factors increase nonlinearly with these parameters. Results indicate that for accurate determination of crack tip fracture parameters when severe thermal gradients are present in the material, it is necessary to consider the variation of thermo-mechanical properties with temperature.